Gender Differences in Financial Decision-Making and Behaviors in Single and Joint Households. (March 2023) - Wagner, Jamie; Walstad, William B.
This study investigates gender differences in household financial behavior using data from the 2018 National Financial Capability Study, a large and nationally representative survey about adults' financial behavior, knowledge, and attitudes. The behaviors include paying your credit card in full each month, having a 3-month emergency fund, having non-retirement investments, and having a non-employer retirement account. Results showed that single females were significantly less likely to engage in any of the financial behaviors compared to men. Additionally, females in joint households were also significantly less likely to engage in the behaviors compared to males. These results are robust when splitting the single and joint household samples by age, level of financial literacy, and using a sample from a prior year. Therefore, females may not be well-prepared for financial decision-making in single or joint households, which can have adverse consequences for managing current personal finances and building wealth for the future. JEL codes: D12, D14, I21